Impacto do controle e gestão familiares sobre a performance das empresas: um estudo sobre indústrias de médio porte - Santos, José Tomás Vieira dos (2009)
The family controlled companies, here defined through the largest property control block belonging to a family, have a significant importance in the economy and in our society. This is reflected in the growing interest in the study of these organizations unique characteristics, as well as if such factors provide more efficiency to their operations. This research proves, using a sample of medium sized industries, that the family controlled companies are so or more efficient than the non family companies, while comparing their financial performance. The family organizations main differentiating elements are analyzed, specially the 'familiness' effect: the characteristics derived from the complex relationship between family and business, and which influence these companies performance. Also, it was examined if this superior performance is affected by the family controlled company management format. Two formats were studied: when the president or most of the management is composed by executives not related to the family, commonly named professional management, and when these functions are concentrated in the hands of the own family, situation named as family management. In this sense, it is not possible to state that the professional management results in a superior performance, as defended in several empiric researches developed in other countries. On the contrary, it is demonstrated that the family management is, at least, as efficient as the professional management, presenting, also, better results in a profitability index. Finally, the different generations’ impact ahead of the family companies’ management is analyzed, proving that, while the founding generation is distinguished in terms of growth, the subsequent generations present better results in terms of profitability, what is coherent to the different moments in the interaction time between family and business.